A Review on Geographical and Pharmacological Distribution of Brassica Oleracea - Deepika Sati; Deepika; Bhatt, Mansi; Kumar, Roshan; Anamika; Upadhyay, Jyotsna; Naaz, Farha; Nyarko, Richard Owusu; Asum, Christian (Journal for Research in Applied Sciences and Biotechnology, 2023)
Background: White cabbage, scientifically known as Brassica oleracea var. capitata f. alba, is a cruciferous vegetable that has long been valued for its culinary and medicinal uses. For the treatment of numerous illnesses, such as diabetes, cancer, inflammation, hypertension, hypercholesterolemia, bacteria, oxidation, and obesity, various preparations derived from various portions of the plant, including roots, shoots, leaves, and the entire plant, are utilized. Objective: Botany, distribution, traditional applications, phytochemistry, and pharmacological properties of B. oleracea var. capitata are all going to be assessed in this review. In addition, the gaps in knowledge will be filled and new research opportunities in pharmacology will be highlighted by this review. Method: Through an internet search of internationally recognised scientific databases, a variety of resources were gathered to gain a comprehensive understanding of Brassica oleracea var. capitata. These resources included research papers, reviews, books, and reports. Results: Alkaloids, flavonoids, organic acids, glucosinolates, steroids, hydrocarbons, and about forty-nine other phytochemical components of Brassica oleracea var. capitata have been culled from various sources. Bactericidal, antioxidant, anti-inflammatory, antibacterial, anti-obesity, anticoagulant, hepatoprotective, and anticancer are only a few of the pharmacological activities exhibited by crude extracts and phytoconstituents of Brassica oleracea var. capitata. Here you may find a complete inventory of the phytochemical components and pharmacological information pertaining to Brassica oleracea var. capitata. Conclusion: Results showed that Brassica oleracea var. capitata is a significant medicinal plant with multiple pharmacological effects, and the study also looked at its phytochemistry, traditional applications, and pharmacological activity. Our goal in conducting this assessment of this plant was to bridge knowledge gaps in the field and lay the groundwork for future studies and medication development. While researching Brassica oleracea var. capitata, we did find a number of significant traditional applications and pharmacological properties.